Student perception on the use of tablet computer in academic library - Noratikah Nordin; Fatimah Hassan (Penerbit Universiti Kebangsaan Malaysia, 2018)
The speed of technology adaptations has made it necessary to provide the latest tools to facilitate students in academic libraries. However, the available library services are not used effectively and efficiently by the students. Unattractive library services have been identified as the problems that make the library incompetent in serving and delivering successful library services to the students. This paper attempted to explore the perception of undergraduate students regarding possible use of tablet computer for library services in the academic library. Quantitative approach is adopted with the structured questionnaire has been distributed to 155 undergraduate students. The result shows that the acceptance of a tablet computer by the students is satisfactory and has a good perception to enhance library services. Many students have responded that the tablet computer is an interactive and innovative way to use library services. This paper makes a significant contribution to the academic library services by clarifying the usefulness of tablet computer and the importance of having ICT application for enhancing library services in Malaysia. This paper provides evidence on the use of ICT application by the undergraduate students in retrieving information and their attitudes toward applying ICT application in the academic library.